Is ultrasonographic enthesitis evaluation helpful for diagnosis of non-radiographic axial spondyloarthritis? - YAĞCI, İLKER (SPRINGER HEIDELBERG, 2018)
The aim of this study is to evaluate the diagnostic utility of ultrasonographic enthesitis assessment in patients with non-radiographic axial spondyloarthritis (nr-axSpA) and to compare different sonographic scoring methods. Patients with nr-axSpA (n=30) and mechanical back pain (MBP) (n=30) were enrolled in the study with standardized clinical criteria. For both of the groups, a total of 18 entheses were evaluated in each patient with B mode ultrasound and power Doppler by a sonographer who is blinded to initial clinical and radiological assessments. Glasgow Ultrasound Enthesitis Scoring System (GUESS), Madrid Sonographic Enthesitis Index (MASEI) and D'Agostino grading system were performed. Intra-rater and inter-rater reliability analyses were evaluated with the intraclass correlation coefficient (ICC). There was at least one enthesitis in 96.7% of patients with nr-axSpA. Median values of the number of enthesitis were 5 in nr-axSpA and 0 in MBP. Mean GUESS total scores were 0.9 in MBP and 4.5 in nr-axSpA. Mean MASEI total scores were 2.3 and 10.5, respectively. The sensitivities were 96.7% and 93.3% for GUESS and MASEI while the detected specificities were 80% for both methods. For Intra-rater reliability analysis, ICC was calculated as 0.981 for GUESS and 0.975 for MASEI, while it was calculated as 0.964 and 0.962 for inter-rater reliability analysis. Thus, evaluation of enthesitis with ultrasound is a reliable, helpful tool for the distinction of patients with nr-axSpA from patients with MBP. We favored the use of MASEI because of assessing upper extremity, using power Doppler and having a correlation with disease activity.
Keywords: Enthesitis; GUESS; MASEI; Non-radiographic axial spondyloarthritis; Ultrasonography; ANKYLOSING-SPONDYLITIS; PERIPHERAL ENTHESITIS; DOPPLER ULTRASOUND; POWER DOPPLER; INDEX; VALIDATION; CRITERIA; TOOL